Planejamento Estratégico para o Sistema de Bibliotecas da Universidade Federal do Amazonas: proposta de modelo - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
Strategic planning allows an accurate diagnosis of reality, encouraging employee participation which is critical in the implementation of actions that contribute to the improvement of services offered. The research aims to propose a strategic planning model to be implemented by the Library System of the Federal University of Amazon (SISTEBIB / UFAM). To achieve the above, the literature review included topics such as strategy, describing concepts already established among specialists, as well as strategic planning, especially its applicability in the environment of non-profit organizations with a view to enlist the use of this in University Libraries (Bus), identifying the macro-strategies applied by units of information, and describe the ten schools of thought on strategy formulation. We selected three strategic planning Systems Brazilian University Libraries, analysis of these and sought to identify the main macro-strategies used by these organizations as well as schools planning more employed by these units of information in order to understand their processes and influences in order to compose a model to be implemented in the University Library System Federal Amazon. The research, exploratory type, was performed through secondary sources, in particular, the literature review and documentary. For the parameter analysis was adopted in order to compose a qualitative descriptive and interpretive result. The proposed model consists of eight stages, which comprise the basic requirements in the process of strategic planning at BU.
Keywords: Biblioteca universitária; Macroestratégias; Planejamento Estratégico; University library; Macrostrategies; Strategic Planning; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO